BFV-Blockchainvoting: blockchain-based electronic voting systems with BFV full homomorphic encryption - Yatao YANG; Deli LIU; Peihe LIU; Ping ZENG; Song XIAO (Tongxin xuebao)
Current electronic voting systems mostly relied on central server and the trusted third party, this kind system architecture increases the security risks of voting, and even makes voting fail.In order to solve this issue, an electronic voting system BFV-blockchainvoting that supported BFV homomorphic encryption was proposed, and this system applied the blockchain technology to the electronic voting system to replace the trusted third party.Firstly, an open and transparent bulletin board was used to record the vote information, and an intelligent contract was used to realize the functions of verification and self counting.Secondly, in order to further improve the security and reliability of the voting process, the voter’s registration information was signed by SM2 signature algorithm, the ballot was managed by both parties that can supervise each other, and the counting data was encrypted by the BFV full homomorphic encryption algorithm.Finally, the evaluation of performance shows that it only costs 1.69 ms to complete one ballot in the proposed electronic voting system.This electronic voting scheme based on the BFV full homomorphic encryption and blockchain has better security attributes such as manipulation-resistance, anonymity, verifiability, double-voting resistance, coercion-resistance and resistance to quantum attacks.The scheme is suitable for a variety of voting scenarios and can meet the efficiency requirements in large voting scenarios.